Implementasi Pembelajaran Akidah Akhlak dalam Membentuk Akhlak Siswa di Madrasah Ibtidaiyah Fathul Huda Grobogan Mojowarno Jombang - Muhtadi Muhtadi; Eko Hadi Wardoyo; Totok Ardiansyah (Fakultas Agama Islam Universitas Darul 'Ulum Jombang, 2024)
This study aims to determine the Implementation of Aqidah Akhlak Learning in Forming Student Morals at Fathul Huda Elementary School Grobogan Mojowarno Jombang. This type of research is a qualitative research that is descriptive in nature. The data collection technique uses interviews, observations and documentation. The data analysis technique uses inductive, deductive and comparative methods. The results of this study based on observations and interviews conducted, show that madrasah students consistently behave in ways that reflect moral values, such as being polite, worshiping with discipline, and interacting with others with a good attitude. They also carry out religious activities such as Dhuha prayer, reciting the Aqidatul Awwam book, Tahlil and Istighosah. Aqidah akhlak education does not only focus on teaching theory, but also applies these values ​​in students' daily lives, in line with character education theories that emphasize the importance of integrating moral values ​​in the curriculum to form individuals who are noble and responsible. The obstacles experienced in students' learning of faith and morals are the influence of social interactions and the use of technology (cell phones). Keywords: Learning Aqidah and Akhlak; Formation of Akhlak